The influence of images on organizational attractiveness: comparing Chinese, Russian and US companies in Germany. Issue 3 (4th February 2018) - Held, Katrin; Bader, Benjamin
Abstract: In developed markets, Emerging Market Multinational Enterprises' (EMNEs) organizational attractiveness may crucially depend on applicants' country and corporate character images (CCIs). Applying image and signaling theory, this study compares the influence of these images on the organizational attractiveness of Chinese, Russian and US companies in Germany. Employing data from 287 German business students, findings show that applicants prefer US over Chinese and Russian companies as future employers, confirming the existence of the liability of emergingness. Moreover, findings indicate gender differences in applicants' attraction toward EMNEs. In particular, female applicants are less attracted to EMNEs with a bad CCI than male applicants are.